Toxic or viral epidermal necrolysis/Staphylococcal epidermal necrolysis (4S) - Bonifazi, E. (European Journal of Pediatric Dermatology, 2003)
Epidermal necrolysis is characterized by large flaccid blisters. The latter are due to hematogenous spread of epidermolytic toxins and thus may affect the entire skin surface. The responsible factors maybe multiple, mainly viruses, drugs and Staphylococcus aureus. In childhood viruses and Staphylococcus aureus are responsible for the most frequent and severe forms. The differential diagnosis is crucial to immediately start antibiotics in the staphylococcal form.